2013
DOI: 10.18632/oncotarget.1295
|View full text |Cite
|
Sign up to set email alerts
|

Immunological targeting of tumor cells undergoing an epithelial-mesenchymal transition via a recombinant brachyury-yeast vaccine

Abstract: The embryonic T-box transcription factor brachyury is aberrantly expressed in a range of human tumors. Previous studies have demonstrated that brachyury is a driver of the epithelial-mesenchymal transition (EMT), a process associated with cancer progression. Brachyury expression in human tumor cells enhances tumor invasiveness in vitro and metastasis in vivo, and induces resistance to various conventional therapeutics including chemotherapy and radiation. These characteristics, and the selective expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 31 publications
1
52
0
Order By: Relevance
“…*p \ 0.05. NS non significant to its role in the EMT process and involvement in metastatic development in solid tumors [17,19], Brachyury is positioned as a promising therapeutic target for advanced cancer patients [40,44]. To our knowledge, this is the first study that investigates Brachyury immunostaining and its relevance as a novel marker of aggressiveness in GIST.…”
Section: Discussionmentioning
confidence: 96%
“…*p \ 0.05. NS non significant to its role in the EMT process and involvement in metastatic development in solid tumors [17,19], Brachyury is positioned as a promising therapeutic target for advanced cancer patients [40,44]. To our knowledge, this is the first study that investigates Brachyury immunostaining and its relevance as a novel marker of aggressiveness in GIST.…”
Section: Discussionmentioning
confidence: 96%
“…Several reports have demonstrated that EMT is critical for prostate cancer progression, as acquisition of mesenchymal features may favor dissemination and resistance to therapy (35). High levels of Brachyury have previously been reported in various types of cancer (5-9, 11) and a phase I clinical trial of a vaccine targeting Brachyury-positive tumors (GI-6301) is currently under way (36,37). Although prostate cancer is a leading cause of cancer-related deaths in men worldwide, a characterization of Brachyury biologic role in prostate tumorigenesis is missing.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, TWIST may also be a viable immunotherapy target; recently TWIST was shown to be a TAA in the TRAMP-C2 subcutaneous model of murine PCa, and combined treatment of TRAMP-C2 xenografts in vivo with enzalutamide and a TWIST-specific vaccine significantly reduced tumor burden . Similarly, the T-box transcription factor Brachyury, which drives EMT in many cancers (Fernando et al 2010), has been identified as another PCa TAA, and yeast-based Brachyury vaccines are currently in development for the treatment of CRPC (Hamilton et al 2013). In addition, targeted therapies are in development to prevent identified drivers of NEPC and checkpoint molecule expression by tumors.…”
Section: Tumor Cell Plasticity: Overlap In Aggressive Cell Phenotypesmentioning
confidence: 99%